Career progression and destinations, comparing men and women in the NHS: Postal questionnaire surveys - Taylor, K; Lambert, T; Goldacre, M (2009)
Objective: To study the career progression of NHS doctors, comparing men and women. Design: Postal questionnaire surveys. Participants and setting: Graduates of 1977, 1988, and 1993 from all UK medical schools. Results: The response rate was 68% (7012/10 344). Within general practice, 97% (1208/1243) of men, 99% (264/267) of women who had always worked full time throughout their career, and 87% (1083/1248) of all women were principals. Median times from qualification to principal status were 5.8 (95% confidence interval 5.6 to 6.0) years for men, 5.6 (5.4 to 5.8) years for women who had worked full time during training, and 6.8 (6.5 to 7.0) years for all women. Of the 1977 and 1988 graduates in hospital practice, 96% (1293/1347) of men were consultants, compared with 92% (276/299) of women who had always worked full time throughout their career and 67% (277/416) of women who had not. Median time to first consultant post was 11.7 (11.5 to 11.9) years for men, 11.3 (11.0 to 11.6) years for women who worked full time during training, and 12.3 (12.0 to 12.6) years for all women. Women who had not always worked full time throughout their career were over-represented in general practice and under-represented in most hospital specialties, substantially so in the surgical specialties and anaesthetics. Women who had always worked full time were under-represented not only in the surgical specialties but also in general practice. Conclusions: Women not progressing as far and as fast as men was, generally, a reflection of not having always worked full time rather than their sex. The findings suggest that women do not generally encounter direct discrimination; however, the possibility that indirect discrimination, such as lack of opportunities for part time work, has influenced choice of specialty cannot be ruled out.